Comparison of pre-workout nitric oxide stimulating dietary supplements on skeletal muscle oxygen saturation, blood nitrate/nitrite, lipid peroxidation, and upper body exercise performance in resistance trained men - Canale Robert E; McCarthy Cameron G; Trepanowski John F; Farney Tyler M; Bloomer Richard J; Schilling Brian K (Taylor & Francis Group, 2010)
Abstract Background We compared Glycine Propionyl-L-Carnitine (GlycoCarn®) and three different pre-workout nutritional supplements on measures of skeletal muscle oxygen saturation (StO2), blood nitrate/nitrite (NOx), lactate (HLa), malondialdehyde (MDA), and exercise performance in men. Methods Using a randomized, double-blind, cross-over design, 19 resistance trained men performed tests of muscular power (bench press throws) and endurance (10 sets of bench press to muscular failure). A placebo, GlycoCarn®, or one of three dietary supplements (SUPP1, SUPP2, SUPP3) was consumed prior to exercise, with one week separating conditions. Blood was collected before receiving the condition and immediately after exercise. StO2 was measured during the endurance test using Near Infrared Spectroscopy. Heart rate (HR) and rating of perceived exertion (RPE) were determined at the end of each set. Results A condition effect was noted for StO2 at the start of exercise (p = 0.02), with GlycoCarn® higher than SUPP2. A condition effect was also noted for StO2 at the end of exercise (p = 0.003), with SUPP1 lower than all other conditions. No statistically significant interaction, condition, or time effects were noted for NOx or MDA (p > 0.05); however, MDA decreased 13.7% with GlycoCarn® and increased in all other conditions. Only a time effect was noted for HLa (p < 0.0001), with values increasing from pre- to post-exercise. No effects were noted for HR, RPE, or for any exercise performance variables (p > 0.05); however, GlycoCarn® resulted in a statistically insignificant greater total volume load compared to the placebo (3.3%), SUPP1 (4.2%), SUPP2 (2.5%), and SUPP3 (4.6%). Conclusion None of the products tested resulted in favorable changes in our chosen outcome measures, with the exception of GlycoCarn® in terms of higher StO2 at the start of exercise. GlycoCarn® resulted in a 13.7% decrease in MDA from pre- to post-exercise and yielded a non-significant but greater total volume load compared to all other conditions. These data indicate that 1) a single ingredient (GlycoCarn®) can provide similar practical benefit than finished products containing multiple ingredients, and 2) while we do not have data in relation to post-exercise recovery parameters, the tested products are ineffective in terms of increasing blood flow and improving acute upper body exercise performance.